Towards a viable roadmap for solar and wind waste recycling in Aotearoa New Zealand - Okebe, Judy; Brent, Alan (Archives of Sustainable Energy Systems, 2025)
Aotearoa New Zealand’s ambition for 100 percent renewable electricity by 2030 and full decarbonisation by 2050 has driven a rapid expansion of solar photovoltaic and wind power generation infrastructure. However, this growth presents a parallel sustainability challenge in the effective management of end-of-life waste management. This study therefore estimates future volumes of renewable energy waste through to 2080 and evaluates the economic potential of material recovery alongside an assessment of relevant policy and infrastructure conditions. Using a mixed-methods approach, quantitative projections based on installation lifespans and material intensity were developed for solar and wind waste streams, and a qualitative analysis of European Union and Australian best practices were undertaken to inform policy recommendations. The results indicate that cumulative waste from utility-scale systems will reach approximately 1.68 million tonnes by 2080, with high-value materials such as aluminium, copper, and steel offering a recoverable economic value of up to NZ$ 11.8 billion. Moreover, the analysis reveals that technical complexity, regulatory gaps, and limited economies of scale currently hinder the development of a local recycling industry. Additionally, our findings suggest that a viable recycling roadmap is achievable through extended producer responsibility schemes, targeted regional infrastructure investment, and integration of circular economy policies. Finally, proactive planning will enable Aotearoa New Zealand to align environmental sustainability with renewable energy deployment and position itself as a leader in the responsible management of clean energy transitions.